2019
DOI: 10.3389/fchem.2019.00791
|View full text |Cite
|
Sign up to set email alerts
|

Neuraminidase-3 Is a Negative Regulator of LFA-1 Adhesion

Abstract: Within the plasma membrane environment, glycoconjugate-receptor interactions play an important role in the regulation of cell-cell interactions. We have investigated the mechanism and activity of the human neuraminidase (NEU) isoenzyme, NEU3, on T cell adhesion receptors. The enzyme is known to prefer glycolipid substrates, and we confirmed that exogenous enzyme altered the glycolipid composition of cells. NEU3 was able to modify the sialic acid content of purified LFA-1 in vitro. Enzymatic activity of NEU3 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 113 publications
4
25
0
Order By: Relevance
“…(Wright & Cooper, 2014) Our previous work has suggested that NEU3 mediates desialylation of gangliosides and glycoproteins which may inhibit cis-interactions with β1 integrins (α4β1 and α5β1; also known as VLA4 and VLA5, respectively). (Howlader et al, 2019;Jia et al, 2016) Here, we confirmed that BMDM from Neu3 KO animals had increased in vitro chemotaxis through a FN-coated membrane, consistent with this isoenzyme acting as a negative regulator of cell migration in response to a chemoattractant (MCP-1/CCL2). In contrast, Neu1 KO animals showed reduced migration in vitro.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…(Wright & Cooper, 2014) Our previous work has suggested that NEU3 mediates desialylation of gangliosides and glycoproteins which may inhibit cis-interactions with β1 integrins (α4β1 and α5β1; also known as VLA4 and VLA5, respectively). (Howlader et al, 2019;Jia et al, 2016) Here, we confirmed that BMDM from Neu3 KO animals had increased in vitro chemotaxis through a FN-coated membrane, consistent with this isoenzyme acting as a negative regulator of cell migration in response to a chemoattractant (MCP-1/CCL2). In contrast, Neu1 KO animals showed reduced migration in vitro.…”
Section: Discussionsupporting
confidence: 74%
“…Activation epitopes of β2 integrins were reported to be unmasked by endogenous NEU activity, (Feng et al, 2011;Quinn et al, 2001) and NEU3 has been shown to alter LFA-1/ICAM-1 interactions. (Howlader et al, 2019) NEU enzymes can increase adhesion of polymorphonuclear leukocytes (PMN) to endothelium and also increase their migration through the endothelium to the site of inflammation. (Cross et al, 2003;Sakarya et al, 2004) NEU enzymes may unmask epitopes in β1 integrins VLA4 (CD49d/CD29) and VLA5 (CD49e/CD29), which are expressed on activated leukocytes and bind with VCAM-1 and fibronectin (FN).…”
Section: Introductionmentioning
confidence: 99%
“…We cultured HeLa GFP cells with a deglycosylating mix of enzymes, thereby promoting its degradation ( Fig. 4A ) ( 34 , 35 ). We confirmed specific enzymatic activity in mammalian medium by digesting fetuin, an N- and O-glycosylated control protein ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We cultured HeLa cells with a deglycosylating mix of enzymes, thereby promoting its degradation (Fig. 4A) 30,31 . We confirmed specific enzymatic activity in mammalian medium by digesting fetuin, a N- and O-glycosylated control protein (Fig.…”
Section: Resultsmentioning
confidence: 99%